Quantitative Studies on Fabrics as Disseminators of Viruses: IV. Virus Transmission by Dry Contact of Fabrics - Sidwell, Robert W. (1970)
Cotton and woolen fabrics and fabrics of synthetic fibers were exposed by direct contact (pipette) and by aerosolization to poliovirus and to vaccinia virus in separate experiments, allowed to dry for 16 hr at 25 C in 35% relative humidity, and randomly tumbled with sterile swatches of the same fabrics for 30 min. By use of a HEp-2 cell assay system, up to 10(3.5) CCID(50) of poliovirus per ml and 10(4.4) CCID(50) of vaccinia virus per ml were recovered from the originally sterile fabrics as early as 1 to 10 min after contact. Maximum transfer of both viruses was achieved with wool blanket material, although high titers of vaccinia virus were recovered from all fabrics tested. Poliovirus placed on the fabrics in an aerosol tended to be transferred to the sterile fabrics at a greater rate than when it was placed on the fabrics by direct contact. The method of exposure had essentially no effect on the rate of transfer of vaccinia virus.